Pendampingan Peningkatan Kemampuan Kewirausahaan Bagi Santri Pondok Pesantren Bustanul Mansuriyah - Hendri Hermawan Adinugraha; Edi Supriyanto; Bahtiar Effendi (Jumat Keagamaan: Jurnal Pengabdian Masyarakat, 2022)
The goal of this service is to expand students’ knowledge and awareness of entrepreneurship at Bustanul Mansuriyah Islamic Boarding School, as well as to assist them open their minds to the possibility of becoming entrepreneurs. The execution of this service uses education, socialization, and entrepreneurship training approaches to open the attitude of being entrepreneurs from an early age, allowing students to achieve economic independence. As a result of the adoption of this service, the majority of Bustanul Mansuriyah Islamic Boarding School students are able to comprehend and practice digital marketing, as well as create simple business plans in groups that are executed in their various businesses. This service’s advice is that all students in Indonesia, starting at a young age, should be educated, socialized, and mentored as Santripreneurs so that they can become economically self-sufficient and create work possibilities for themselves and society generally.